Toll-Like Receptor Transcriptome in the HPV-Positive Cervical Cancer Microenvironment - Correne A. DeCarlo; Bruce Rosa; Robert Jackson; Sarah Niccoli; Nicholas G. Escott; Ingeborg Zehbe (Clinical and Developmental Immunology)
The human papillomavirus (HPV) directly infects cervical keratinocytes and interferes with TLR signalling. To shed light on the effect of HPV on upstream receptors, we evaluated TLRs 1–9 gene expression in HPV-negative normal and HPV-positive pre-malignant and malignant ex vivo cervical tissue. Quantitative real-time polymerase chain reaction was performed separately for epithelial and stromal tissue compartments. Differences in gene expression were analyzed by the Jonckheere-Terpstra trend test or the Student's t-test for pairwise comparison. Laser capture microdissection revealed an increase in TLR3 and a decrease in TLR1 mRNA levels in dysplastic and carcinoma epithelium, respectively. In the stroma, a trend of increasing TLR 1, 2, 5, 6, and 9 mRNA levels with disease severity was found. These findings implicate the involvement of TLR3 and TLR1 in early and late cervical carcinogenesis, respectively, suggesting that stromal upregulation of TLRs may play a role in cervical disease progression.